TEACHING WRITING DESCRIPTIVE TEXTS THROUGH MIND MAPPING COLLABORATIVE WRITING TECHNIQUES - Sijono, Sijono; Sutapa, Gatot; ., Sudarsono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research aimed at improving students? ability in writing descriptive text through mind mapping collaborative writing technique. The data were taken from students of X B in SMA Nusantara Indah Sintang in the Academic Year 2016-2017. The finding showed that this technique could make the students enjoyed the writing activity and generated the students? motivation to get involved in the writing process. The students were happy worked collaboratively with other student; moreover, the students could share their difficulties among the activity. Mind mapping collaborative writing could help the students to improve their writing descriptive texts and motivate the students to be active in the writing activity. Mind mapping collaborative writing is suggested to use in teaching writing. Keywords: Teaching Writing, Mind Mapping Collaborative Writing, Writing Descriptive Texts. Abstrak, Penelitian ini bertujuan untuk meningkatkan kemampuan siswa/siswi dalam menulis teks deskriptif melalui tehnik ?mind mapping collaborative writing? pada siswa/siswi SMA Nusantara Indah Sintang, kelas XB tahun pelajaran 2016/2017. Hasil penelitian ini menunjukan bahwa tehnik ini dapat membuat siswa merasa nyaman dan memicu motivasi mereka dalam kegiatan menulis. Para siswa senang bekerja sama denga siswa lainnya, terlebih mereka dapat saling berbagi kesulitan selama kegiatan menulis. Tehnik ?mind mapping collaborative writing? dapat membantu siswa meningkatkan kemampuan menulis teks deskriptif dan dapat memotivasi siswa untuk berperan aktif dalam kegiatan menulis. Tehnik ?mind mapping collaborative writing? disarankan untuk dapat digunakan dalam belajar menulis.Kata kunci: Belajar Menulis, Mind Mapping Collaborative Writing, Menulis Teks Deskriptif.